Predicting abstinence from methamphetamine use after residential rehabilitation: Findings from the Methamphetamine Treatment Evaluation Study. (18th April 2017) - McKetin, Rebecca; Kothe, Astrid; Baker, Amanda L.; Lee, Nicole K.; Ross, Joanne; Lubman, Dan I.
Abstract: Introduction and Aims: We previously found that residential rehabilitation increased continuous abstinence from methamphetamine use 1 year after treatment. We examine what client and treatment characteristics predict this outcome. Design and Methods: Participants (n = 176) were dependent on methamphetamine and entering residential rehabilitation for methamphetamine use. Simultaneous logistic regression was used to identify independent predictors of continuous abstinence from methamphetamine use at 1 year follow‐up. Measures included demographics, drug use, psychiatric comorbidity (Diagnostic and Statistical Manual of Mental Disorders, major depression, social phobia, panic disorder, schizophrenia, mania and conduct disorder), symptoms of psychosis and hostility, readiness to change, motivations for treatment and treatment characteristics (duration, rapport, group and individual counselling). Results: Participants stayed in treatment for a median of 8 weeks; 23% remained abstinent at 1 year. The only independent predictors of abstinence were more weeks in treatment [adjusted odds ratio (AOR) 1.2, P < 0.001], better rapport with treatment providers (AOR 2.4, P = 0.049) and receipt of individual counselling (AOR 3.7, P = 0.013), whereas injecting methamphetamine predicted not achieving abstinence (AOR = 0.25, P = 0.002). Individual counselling and good rapport increased abstinence to 45%; for injectors, longer stays in treatment (13+ weeks) were additionally needed to produce similar abstinence rates (43%). Discussions and Conclusions: Abstinence from methamphetamine use following residential rehabilitation could be significantly increased by providing individual counselling, maintaining good rapport with clients and ensuring longer stays for people who inject the drug. [McKetin R, Kothe A, Baker AL, Lee NK, Ross J, Lubman DI. Predicting abstinence from methamphetamine use after residential rehabilitation: Findings from the Methamphetamine Treatment Evaluation Study. Drug Alcohol Rev 2018;37:70–78]